"You Don't Fit in Here": Navigating Relatives' Visits During Study Abroad. Issue 3 (1st July 2022) - COMPIEGNE, IRWIN
Abstract : Visiting friends and relatives (VFR) is long established as a major motive for travel. While VFR has received significant scholarly attention especially in the marketing and tourism literature, its implications on study abroad students' experiences are understudied. This study, based on a longitudinal digital ethnography of seven Australian university students learning French in France or Switzerland, reveals that visits from participants' relatives had significant impacts on their study abroad experience and their identity transition to adulthood. Findings indicate that, first, to different extents, the presence of the relatives in participants' host environment caused disturbances in their daily routine and recently acquired independence highlighting participants' ongoing transition to adulthood. Second, reintegration into their family dynamic resulted in two opposing consequences: while some participants had to readjust to being a child, which impeded their transition to adulthood, others were placed in a position of power within the family due to their greater knowledge and experience of the target language and the host environment. Last, visits forced participants to anticipate their return to their family home resulting in increasing stress and apprehension.